Nurses’ roles in continuity of care implementation for coronary artery bypass graft patients - Depari, Syella Elnida; Dewi, Wan Nishfa; Putri, Syeptri Agiani (University of Muhammadiyah Malang, 2024)
Introduction: The roles of nurses in implementing continuing care in Coronary Artery Bypass Graft (CABG) patients have an essential part in improving patients' quality of life. Objectives: This study aims to determine nurses's roles in continuity of care implementation for CABG patients. Methods: This study employed a descriptive research design. The sample of this study was all nurses working at the CABG wards at the Arifin Achmad Hospital, who were selected using a total sampling technique. The variables measured in this study are the role of nurses, including caregivers, communicators, educators, client advocates, and counsellors. Data were collected using a questionnaire developed by the researcher that had been tested before use. The data analysis used is descriptive analysis, which presents the percentage of variables measured. Results: Demography characteristics from 37 nurses depict the majority of respondents in the age range of 36-45 years (45.4%), with the majority of women (81.1%), most nurses' education background is registered nurse (56.8%), and the majority of work experience is ≥ 12 years (64.9%). This study's findings showed the role of nurses as good caregivers (56.8%), good communicators (75.5%), good educators (67.6%), good client advocacy (73%), and good counsellors (51.4%). Conclusions: It can be concluded that most nurses perform an adequate role in implementing continuity of care in CABG patients. Then, it will reduce re-hospitalisation risk and improve the quality of life for patients with CABG.